Chronic Expanding Hematoma in the Extremities: A Clinical Problem of Adhesion to the Surrounding Tissues. (31st May 2017) - Sakamoto, Akio; Okamoto, Takeshi; Matsuda, Shuichi
Abstract : Chronic expanding hematoma is characterized by continuous growth of a blood collection. We analyzed the clinical features of 7 patients with chronic expanding hematomas in the extremities, with an average age of 65.6 years. All lesions occurred in the lower extremities, with 4 seen in the thigh and 3 in the knee region. Six patients had subcutaneous hematomas, while 1 was deep-seated in the thigh. The magnetic resonance features of the lesion were compatible with those of a standard hematoma. A low signal intensity on T1- and T2-weighted imaging at the pseudocapsule was also characteristic. Cystic features were seen in 5 of 7 patients. All lesions were resected together with their pseudocapsule. In the subcutaneous lesions, it was necessary to resect adherent fascia, with or without involved skin. In the deep-seated thigh lesion, the common peroneal nerve was completely adherent to the pseudocapsule, a phenomenon from absence of the common peroneal nerve which appeared after resection. Chronic expanding hematomas of the extremities are predominantly located in the subcutaneous tissue of the lower extremity. The surrounding pseudocapsule is adherent to the adjacent tissues, and clinicians must be aware of this, especially when resecting a deep-seated lesion.